Expanded graphite enhanced cellulose aerogel/palmityl alcohol composite phase change material with effective thermal energy storage properties - Erol, Tugcenur Bayraktar; Sari, Ahmet; Can, Ahmet; Kaya, Mehmet; Sharma, R. K.; Gençel, Osman; Tyagi, V. V.; Gençel, Osman; Can, Ahmet (Elsevier, 2025)
Advanced phase change materials (PCMs) play a critical role in enhancing the efficiency of thermal energy storage (TES) systems.In this study, a non-leaching composite PCM was developed by impregnating palmityl alcohol (PAL) into a hybrid structure composed of cellulose aerogel (CAG), derived from blueberry plant waste, and expanded graphite (EG). The microstructure, chemical composition, latent heat storage (LHS) properties and thermal stability of the seepage-free CAG/PAL/EG composite PCM were characterized by DSC (differential scanning calorimetry), FTIR (Fourier-transform infrared spectroscopy), TGA (thermogravimetric analysis), and thermal conductivity (TC) measurements. The composite PCM showed no leakage during the solid-liquid phase transition when the PAL PCM loading was maximum 50 % rate in the presence of 10 % EG. CAG/PAL(50 %)/EG (10 %) composite showed the highest latent heat storage (LHS) capacity with 147.1 J/g melting enthalpy and 146.3 J/g freezing enthalpy. The addition of EG to the CAG significantly enhanced the thermal conductivity (TC) by 152.9 % and also increased the enthalpy values of the final composite. FTIR results confirmed the physical adsorption of PAL in the pores of CAG. TGA and cycling test results demonstrated that CAG/PAL/EG composite had high thermal stability and excellent thermal reliability over 600 cycles. The synthesized CAG/PAL/EG composite shows promise as a PCM for thermal management in battery units, electronic devices, photovoltaic systems, food drying systems, and waste heat storage and release applications. Furthermore, the usage of CAG in production of seepage-free PCM presents environmental benefit such as disposal of wastes resulting from the pruning of cellulose-based woody plants.
Keywords: Cellulose Aerogel; Palmityl Alcohol; Expanded Graphite; Thermal Energy Storage; Thermal Conductivity